Implementation of Life Skills Education Learning in Realizing Gender Equality in Students of SMPN 2 Ajangale, Bone Regency - Sarifa Suhra; Arifuddin Arifuddin; Sarifa Nursabaha; Sarifa Halijah (Journal of Research and Multidisciplinary, 2021)
The purpose of this article is to show how the life skills education curriculum has helped students at SMPN 2 Ajangale in Bone Regency achieve gender equality. This study is categorized as qualitative. There were two types of data used in this study: primary data and secondary data. Purposive sampling was used to select the informants, which means only utilizing persons who actually understand the situation, such as trainers, school principals, trained instructors, students, and parents' representatives. Secondary data, is a source that is not directly from the informant, but through a search in the form of important documents related to research. The results showed that LSE learning consisted of 5 modules divided into 22 themes/meetings taught in 2 semesters instilling 13 skills, namely; the ability to self-regulate, creativity, critical thinking, making decisions, negotiating, collaborating, solving problems, participating, managing emotions and stress, resilience/resilience to life's tests, empathy, communication, and respect for differences. Meanwhile, the Implementation of Gender Equality in SMP 2 Ajangale Students, Bone Regency, can be seen in 4 aspects, namely; students have access to equal education between boys and girls, have the same opportunity to actively participate without discrimination, involve students fairly, both boys and girls, in exercising control over school policies, all students have the right to benefit from progress education